2015
DOI: 10.1002/mame.201400348
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Behaviors of Modified Poly(ethylene terephthalate) and Their Self‐nucleation Ability

Abstract: A poly(ethylene terephthalate) (PET)/allylisobutyl polyhedral oligomeric silsesquioxanes (a‐POSS) nanocomposite is prepared by a solvent‐casting method and as‐received PET (asr‐PET) is modified by a precipitation method to yield precipitated PET (p‐PET). Their crystallization behaviors have been studied, and both modification methods improved the crystallization temperatures and crystallinities of PET. They were subsequently used to further nucleate asr‐PET at 1 and 5 wt% levels to form self‐nucleated PETs, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The vibration peak of C═O at 1712 cm ‐1 and CH 2 at 1413 cm −1 were significantly enhanced. The bonds at 723 and 2975 cm −1 corresponded to the out of plane bending vibration of CH bonds in aromatic ring of PET molecular chain 29–31 . Also, due to the effect of KH550, the NH bending vibration peak appeared near 1650 cm −1 , and the stretching vibration peak of the OH bonds at 3400 cm −1 was extremely strong, causing the NH stretching vibration peak nearly 3360 cm −1 to be masked 15,32 .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The vibration peak of C═O at 1712 cm ‐1 and CH 2 at 1413 cm −1 were significantly enhanced. The bonds at 723 and 2975 cm −1 corresponded to the out of plane bending vibration of CH bonds in aromatic ring of PET molecular chain 29–31 . Also, due to the effect of KH550, the NH bending vibration peak appeared near 1650 cm −1 , and the stretching vibration peak of the OH bonds at 3400 cm −1 was extremely strong, causing the NH stretching vibration peak nearly 3360 cm −1 to be masked 15,32 .…”
Section: Resultsmentioning
confidence: 98%
“…The bonds at 723 and 2975 cm À1 corresponded to the out of plane bending vibration of C H bonds in aromatic ring of PET molecular chain. [29][30][31] Also, due to the effect of KH550, the N H bending vibration peak appeared near 1650 cm À1 , and the stretching vibration peak of the O H bonds at 3400 cm À1 was extremely strong, causing the N H stretching vibration peak nearly 3360 cm À1 to be masked. 15,32 The above results confirmed that KH550-modified SiO 2 nanoparticles with CH 3 successfully adhered to the surface and reducing the surface energy of the PET fiber.…”
Section: Analysis Of Surface Element and Crystal Structurementioning
confidence: 99%
“…8,9 Thus, enhancing melt strength and improving crystallization rate of PET has become a meaningful proposition. 10 The commonly used nucleating methods for enhancing the crystallization properties include inorganic nucleating agent, [11][12][13][14][15] organic nucleating agent 16,17 and polymer nucleating agent. [18][19][20] Inorganic nucleating agents (silica, mica, zinc oxide, carbon nanotubes, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 , 2 , 3 , 4 , 5 ]. Its low crystallization rate at normal mold temperatures and inherent brittleness characteristics limits the wide application of PET [ 6 , 7 , 8 , 9 ]. A variety of inorganic substances are commonly added at small concentrations to produce high crystallinity and rapid crystallization rate [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%